(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
French literature has always paid special attention to the depiction of the inner world of human beings. It is not limited to the narration of events, but deeply explores the hidden layers of consciousness, moral conflicts, inner contradictions, and existential uncertainty. In this process, language occupies a central place as the main means of expressing thought and emotion.